Cooperativas de trabalho e o retrocesso social decorrente da Lei n. 12.690/2012 - Amorim, Ana Paula Machado (2018)
The cooperative movement was born during the industrial revolution opposing economic liberalism. It was the subterfuge found by the workers to face the misery that was imposed on them through a management model capable of solving the economic and social problems. Cooperatives were born based on principles and values based on the solidarity and appreciation of both its members and the community in which they are inserted. The movement has grown internationally and its importance throughout history has been so expressive that it has resulted in the creation of the International Cooperative Alliance (ICA), a non-governmental and independent association whose main function is to preserve and defend cooperative principles. In Brazil, the Constitution of 1891 mentioned for the first time the possibility of a lawful association between people, which objectively allowed the emergence of cooperativism. In the 1970s, the cooperative system as a whole was regulated through Law N. 5,764/1971. In 1994, Law N. 8,949 added the sole paragraph to art. 442 of the CLT, making it clear that there is no employment relationship between the cooperative society and its members, or between these and the borrowers of their services. Faced with such a situation, in Brazil, over the decades, the exacerbated growth of false cooperatives and their uses as a form of cost reduction have been seen. In this context, Law N. 12,690/2012 was sanctioned in July 2012, which began to regulate the functioning of labor cooperatives, establishing new obligations and provisions other than those provided for in Law N. 5,764/1971. Considering these changes in the legal framework that govern cooperative labor societies, this dissertation analyzes Law N. 12.690/2012, discussing their incongruities and regression in the face of the insertion of innocuous obligations that allow the commodification of human labor.